Kajian Teologis: Tentang Konsep Kasih terhadap Sesama dalam Injil 1 Yohanes 4:7-8 dan Relevansinya bagi Umat Kristiani - Andrika Telaumbanua; Naomi Wahyuni Samangilailai; Windya Permai Br Sirait (Jurnal Magistra, 2024)
This writing is motivated by the phenomenon of love that is not owned by Christians, so that there is a tendency of materialism among Christians that affects the way of thinking and behavior, this is because Christians are not able to carry out religious values perfectly. The emergence of cases of persecution, and discrimination against others shows that there is still a lack of love between people, especially Christians. Therefore, this study aims to apply theological studies on the concept of love for others in the Gospel of 1 John 4: 7-8 and its relevance for Christians, by providing forgiveness to others. By using a qualitative approach method to analyze, study and deepen it so that the right steps are obtained in practicing love for others in everyday life. The results of this study show that, (1) Jesus showed love regardless of ethnic or social differences, (2) Love is selfless, unselfish and most importantly unconditional, meaning total love. Thus, love is shown not only in words, but every real action as shown by Jesus to the Samaritan woman in John 4:7-8.